An Automated Prototype System for Alcohol Level Detection in Drunk Drivers and Vehicle Control. - Akanni, J.; Adewusi, B.; Isa, A. A.; Alao, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Drunk driving is one of the principal contributors to road accidents in Nigeria. Passengers, other motorists and the driver’s life are all at risk because of this behavior. The aim of this study is to develop a system that will automatically detects drunken drivers based on the proximity to the steering wheel and prohibits the car from been start. The method employed in this research is the use of an MQ-3 sensor to measure the level of alcohol in the driver’s breath in the area around where the driver sits in a car and compare it to the Nigerian guidelines for acceptable blood alcohol concentration (BAC) levels. In addition, the alcohol sensor is protected from obstruction (coverage) by an MH infrared proximity sensor. Also, a red light alert is incorporated to sensitize the passenger whenever the driver is drunk. The result shows that the system performed satisfactorily. It prompt quicker reaction by prohibition of drunk drivers within a distance of 36 cm from the steering wheel from being able to start the car as well as sensitizes the passenger through blinking red light. It also prevent the systems sensor from been cover (obstruction) by drunk drivers within a distance of 5 cm. As a result, the system can be combined with the new technologies of modern vehicles to enforced don’t drive when drunk rules which are often violated by drunk drivers.